Relationship between braking intensity and driver heart rate as a function of the size of the measurement window and its position. (April 2023) - Hirsh, Tehila; Sahar, Yotam; Musicant, Oren; Botzer, Assaf; Shoval, Shraga
Highlights: Physiological indices are estimated from physiological signals using time windows. We estimated drivers' HR during braking events with 70 different time windows. The 70 windows' centers were placed at the onset, peak, and end of braking events. Relationships between braking intensity and HR depended on window size and position. Estimations of physiological indices can benefit from exploring window settings. Abstract: Heart Rate (HR) is often used to capture the driver's mental workload and stress. Usually, during a predefined time window (e.g., 10 s, 30 s, or longer). In addition, the center of that time window is commonly placed at the peak of events of interest (e.g., safety events such as hard braking). However, the choices of window size and window position relative to driving events are often not explained in the literature, and conceivably, other choices could have been made for estimating changes in HR. This research tested the effect of window size and position on HR estimates. Participants executed 12 braking events on a closed driving course and were monitored for HR and skin conductivity. We fitted a regression model on HR as a function of driver braking intensity, multiple times (N = 210), each time, we calculated the HR with different window sizes (1–70 s) and three window positions (onset of braking, peak deceleration, and end of braking). We found that the coefficients in the model on HR by braking intensity changed as a function of the window size and its position. Our sample's optimal time window size was different from conventional settings: it was 4-second long and centered at the end of the braking events. Our findings showcase the analysis procedure that we employed and can contribute to research on physiological markers (HR and others) and to the design of driver assistance systems.